2011
DOI: 10.3386/w17166
|View full text |Cite
|
Sign up to set email alerts
|

How Do Mortgage Subsidies Affect Home Ownership? Evidence from the Mid-century GI Bills

Abstract: The largest 20th-century increase in U.S. home ownership occurred between 1940 and 1960, associated largely with declining age at first ownership. I shed light on the contribution of coincident government mortgage market interventions by examining home loan benefits granted under the World War II and Korean War GI Bills. The impact of veterans' housing benefits on home ownership is positive for young men, and declines with age. Veterans' benefits increased aggregate home ownership rates primarily by shifting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 8 publications
1
29
0
Order By: Relevance
“…Numerous economic studies found GI Bill benefits from World War II (WWII), the Korean War, and the Vietnam War increased aspects of socio-economic status (SES) such as education [5-8], income [9-11], occupational status [9,11], and homeownership [12]. Past work found men from disadvantaged backgrounds disproportionately benefit [8-11], while others argue most benefits accrued to men from advantaged backgrounds [5].…”
Section: Purposementioning
confidence: 99%
“…Numerous economic studies found GI Bill benefits from World War II (WWII), the Korean War, and the Vietnam War increased aspects of socio-economic status (SES) such as education [5-8], income [9-11], occupational status [9,11], and homeownership [12]. Past work found men from disadvantaged backgrounds disproportionately benefit [8-11], while others argue most benefits accrued to men from advantaged backgrounds [5].…”
Section: Purposementioning
confidence: 99%
“….8 1985 1987 1989 1991 1993 1995 1997 1999 2001 2003 2005 2007 2009 1985 1987 1989 1991 1993 1995 1997 1999 2001 2003 2005 2007 2009 198519871989199119931995199719992001200320052007200920112013 .4…”
Section: A2 Robustness Checks For Debt-income Regressionsmentioning
confidence: 99%
“…This estimated difference is interpreted as the a point in time. See, for example, Fetter (2013) and Hausman and Rapson (2017) who discuss RD using a time running variable more generally. 10 See Imberman and Lovenheim (2015) for a related design that uses a difference-in-differences (DD) approach to estimate the effect of a sudden news release of school ratings on home prices.…”
Section: Baseline Rd Approachmentioning
confidence: 99%